AB1348 Heterogeneity of patients with anticentromere antibodies. (23rd January 2014) - Belloli, L.; Crotti, C.; Ughi, N.; Massarotti, M.; Marasini, B.
Abstract : Background: Anticentromere antibody (ACA) are considered a serological marker of systemic sclerosis (SSc), in particular of its limited form (lcSSc). They are rarely observed in other connective tissue diseases, but seldom are found associated with primary biliary cirrhosis (PBC). Objectives: To evaluate the clinical heterogeneity of patients with anticentromere antibodies (ACA). Methods: One hundred of patients sent to our Center because of ACA positivity, were retrospectively analyzed. There were 99 females with a follow-up period of at least 5 years. Results: All patients had an autoimmune disease. Eighty-four had systemic sclerosis (SSc): 71 had lcSSc, 8 diffuse SSc (dcSSc) and 5 SSc sine scleroderma. In 17 patients (20.2%) SSc was associated with other autoimmune diseases, mostly with PBC (12 patients, 9 with lcSSc) and autoimmune thyroiditis (7 patients, 6 lcSSc). Two patients had SSc in overlap with rheumatoid arthritis (RA) and Sjögren's syndrome (SS), respectively. Sixteen patients did not have SSc, but other rheumatic diseases: 9 had Undifferentiated Connective Tissue Disease, 2 Systemic Lupus Erythematosus, 2 SS and 2 RA in overlap with SS. Conclusions: The presence of ACA does indicate an autoimmune disorder, mainly lcSSc, often in overlap with PBC. Therefore, the presence of ACA should deserve further examination, because marker of autoimmune disease. Disclosure of Interest: None Declared